The history and evolution of homeland security in the United States : from the Constitution through 9/11 to the present - MacMartin, Steven M.; Silva, Aida T.; Vázquez, Isabel Patricia; Lee Werner, Rodger, Jr (CRC Press, [2025], 2025)
The History and Evolution of Homeland Security in the United States provides a comprehensive and insightful look into the evolution of US Homeland Security, from its early roots to the post-9/11 era. Drawing on their extensive experience as law enforcement professionals, the authors offer a unique perspective on the challenges and triumphs of this critical field. Students seeking degrees - with the goal of a career - in homeland security roles need a comprehensive and foundational understanding of the history of the Department of Homeland Security (DHS) and its predecessor agencies. This includes a detailed accounting of the elaboration of security policies and strategies as they developed in the United States, both before and after the formation of DHS, highlighting the challenges posed by both natural and human-caused threats. Beyond a historical retrospective, this book equips students with the critical thinking and analytical skills necessary to assess the effectiveness of past and present homeland security initiatives. By understanding the historical context, students can better navigate the complex issues surrounding privacy, border security, critical infrastructure protection, and more. As future professionals, students need that historical perspective in order to inform their understanding of current debates and controversies surrounding homeland security. The History and Evolution of Homeland Security in the United States provides a foundational understanding to foster critical thinking, analytical skills, and decision-making - helping the reader gain a historical perspective on the Department, its components, and policies to inform future thought leaders.
Keywords: National security -- United States -- History.; elektronické knihy; electronic books